Implementasi Manajemen Kurikulum Pesantren dalam Membentuk Karakter Mandiri Santri - Maulana, Irfan; Sa’diyah, Maemunah; Bahruddin, Bahruddin (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Forming an independent character in students is a challenging task as they are accustomed to receiving attention and being dependent on their parents, which can result in them becoming spoiled and lazy when they enter the environment of Islamic boarding schools. Hence, it is crucial to have effective curriculum management to foster the development of students' independent character. The aim of this study was to examine the implementation of curriculum management at the Primago Modern Islamic Boarding School and the strategies employed to shape students' independent character. A qualitative approach with a descriptive research design was employed, and data were collected through descriptions and illustrations. The findings revealed that the management of the pesantren curriculum is closely associated with the management functions known as POAC: planning, organizing, implementing, and evaluating. These functions have been successfully implemented at the Primago Modern Islamic Boarding School. Moreover, efforts to nurture students' independent character at the school include programs such as fish farming and entrepreneurship, along with the cultivation of habits that encourage students to undertake various activities independently while being closely supervised by the boarding school caretakers. The implication is that the development of this independent character will equip students with valuable skills and qualities for their future lives beyond the boarding school environment, allowing them to become self-reliant individuals.